Chromosome 5P of Agropyron cristatum induces chromosomal translocation by disturbing homologous chromosome pairing in a common wheat background - Haiming Han; Xinyuan Ma; Zhen Wang; Kai Qi; Wenjing Yang; Weihua Liu; Jinpeng Zhang; Shenghui Zhou; Yuqing Lu; Xinming Yang; Xiuquan Li; Lihui Li (Crop Journal, 2023)
Wide hybridization is a strategy for broadening the genetic basis of wheat. Because an efficient method for inducing wheat–alien chromosome translocations will allow producing useful germplasm, it is desirable to discover new genes that induce chromosomal variation. In this study, chromosome 5P from A. cristatum was shown to induce many types of chromosomal structural variation in a common wheat background, including nonhomoeologous chromosome translocations, as revealed by genomic in situ hybridization, fluorescence in situ hybridization, and DNA marker analysis. Aberrant meiosis was associated with chromosomal structural variation, and aberrant meiotic behavior was observed in wheat–A. cristatum 5P monosomic and disomic addition lines, suggesting that the effect of chromosome 5P was independent of the number of chromosome 5P copies. Chromosome 5P disturbed homologous chromosome pairing at pachytene stage in a common wheat background, resulting in a high frequency of univalent formation and reduced crossing over. Thirteen genes involved in DNA repair or chromatin remodeling, including RAD52-like and MSH6 genes, were differentially expressed (upregulated) in wheat–A. cristatum 5P addition lines according to transcriptome analysis, implicating chromosome 5P in the process of meiotic double-strand break repair. These findings provide a new, efficient tool for inducing wheat–alien chromosome translocations and producing new germplasm.